(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
The formation of a digital economy on a global scale has an impact on the development of all aspects of society. Under the influence of digital technological solutions, production and business processes and the social sphere of society are changing. Digital development also has a huge impact on the competitiveness of companies, including the improvement of their production activities. The article discusses the main directions for improving the activities of companies in the context of digital transformation of the economy.In this article, the authors provide an analysis of various methods and problems of information systems integration, and present the advantages and disadvantages of one or another method.